PELATIHAN PEMBUATAN GREEN PELLET CONCENTRATE PADA KELOMPOK TANI TERNAK MILENIAL (KATEME) - Andi Sukma Indah; Riskayanti Riskayanti; Nurfadilah Nurfadilah; Andi Tenri Darhyati; Rani Juita; Lajuk Arif A; Miranda Miranda; Muhammad Yunus Triadi; Rahma Yutia (Jurnal AbdiMas Nusa Mandiri, 2026)
The Millennial Livestock Farmer Group (KATEME) continues to practice traditional livestock management, with feeding strategies that fail to meet the nutritional requirements of cattle and goats in terms of both quality and quantity, resulting in low productivity and poor reproductive performance. Although leguminous forages are abundant during the rainy season, their availability is highly seasonal, highlighting the need for forage processing and preservation technologies to ensure a sustainable supply of high-quality feed throughout the year. This community service activity aimed to improve farmers’ knowledge and skills through training on the production of green pellet concentrate for the Millennial Livestock Farmer Group (KATEME) in Lalampanua Village, Majene Regency. The main problem faced by the partners was the limited use of feed technology and dependence on fresh forage. The method included needs assessment, counseling, demonstration, hands-on practice in pellet production, as well as monitoring and evaluation using pre-test and post-test. The results showed an increase in participants’ understanding from an average of 33% to 68%, along with improved practical skills in pellet production. This technology enables the utilization of local feed resources into more durable and nutritionally balanced feed, helping maintain feed availability, especially during the dry season. Therefore, green pellet concentrate training serves as an innovative solution for more efficient and sustainable livestock feed management.